Mapping Ethical Consumption Patterns in Halal Cosmetics Using Data-Driven Clustering - Prasetya, Prita; Najib, Mukhamad; Mahliza, Febrina; Darmawan, Teuku Fajar Akbar (Suhuf: International Journal of Islamic Studies, 2026)
Background: The growing demand for halal cosmetic products reflects increasing ethical awareness among Muslim consumers. Understanding how ethical consumption patterns are formed is essential for businesses operating along the halal value chain, particularly in the era of artificial intelligence (AI)-driven decision-making. Objective: This study aims to map ethical consumption patterns in halal cosmetic products using a data-driven clustering approach and to examine their implications for B2B marketing strategies. Methodology: Survey data were collected from halal cosmetic consumers in Indonesia using a Likert-scale instrument. Ethical consumption scores were constructed by integrating halal awareness, halal literacy, attitudes, subjective norms, perceived behavioral control, social influence, intention, and behavior. An exploratory K-Means clustering analysis, supported by the Elbow Method, was applied to identify optimal consumer segments based on data patterns. Results: The findings reveal three distinct clusters reflecting varying levels of ethical orientation. The first cluster demonstrates strong internalization of halal values and consistent alignment between intentions and behavior. The second cluster highlights the influence of cognitive and normative factors, while the third cluster is characterized by relatively weaker ethical commitment and greater external influence. Implications: Ethical consumption in halal cosmetics is primarily driven by internal values rather than social pressure. These insights support the development of targeted segmentation and distribution strategies, as well as AI-based supply chain collaboration aligned with Islamic ethical principles.